FILM DOKUMENTER SEBAGAI MEDIA INFORMASI KOMPETENSI KEAHLIAN SMK NEGERI 11 SEMARANG - Arie Atwa Magriyanti; Hendri Rasminto (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
SMK Negeri 11 Semarang is a school that has four competency skills, namely Graphic Preparation, Graphic Production, Multimedia, and Animation. Every time they enter the beginning of the school year, school socialization and skills competencies are carried out to new students through the Student Orientation Period, using the lecture method from each of the Head of Skills Competencies. Researchers have created an attractive and informative audio-visual presentation media, packed with docudrama stories, namely documentary films. The results of validation tests conducted by expert experts and users show that the documentary films that have been developed by researchers fall into the very good criteria with a percentage of 93.75%. In addition, through the use of the 228 new students as respondents, it can be concluded that the documentary film developed by the author falls into the good criteria with a percentage of 61%.